Civil War in Syria: the psychological effects on journalists. Issue 1 (12th January 2015) - Feinstein, Anthony; Starr, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – More journalists died in Syria during 2013 than in any other country experiencing conflict. This statistic raises concerns about the psychological wellbeing of journalists covering the internecine violence. The paper aims to discuss this issue. Design/methodology/approach – The study sample was made up of 59 western journalists currently covering the Syrian conflict. To place these results in the broader context of war journalism previously collected data from a group of 84 journalists who had reported the war in Iraq were used as a control sample. Outcome measures included indices of posttraumatic stress disorder (PTSD) (Impact of Event Scale-revised) and psychological distress (General Health Questionnaire-28 item version (GHQ-28)). Findings – Compared to journalists who covered the Iraq war, the journalists working in Syria were more likely to be female (p=0.007), single (p=0.018), freelance (p=0.0001) and had worked fewer years as a journalist (p=0.012). They were more depressed according to the GHQ-28 (p=0.001) and endorsed more individual symptoms of depression including worthlessness (p=0.012), helplessness (p=0.02) and suicidal intent (p=0.003). A linear regression analysis revealed that the group differences in depression data could not be accounted for by demographic factors. Research limitations/implications – An absence of structured interviews. Results not applicable to local Syrian journalists. Practical implications – Western journalists covering Syrian appear to be particularly vulnerable to the development of depression. Journalists and the news organizations that employ them need to be cognizant of data such as these. Given that depression is treatable, there needs to be a mechanism in place to detect and treat those in need. Originality/value – This is the first study that highlights the emotional toll on western journalists covering the Syrian conflict.